Respuesta :

Answer:

[tex]g(x)=\frac{x-12}{4}[/tex]

Step-by-step explanation:

To find the inverse of y=4x+12, all you need to is swap x an y and then remake y the subject.

y=4x+12

Swap x and y:

x=4y+12

Solve for y:

Subtracting 12 on both sides:

x-12=4y

Dividing 4 on both sides:

[tex]\frac{x-12}{4}=y[/tex]

So [tex]g(x)=\frac{x-12}{4}[/tex]

Answer:

[-12 + x]\4 = g(x)

Step-by-step explanation:

  1. x = 4y + 12 [SWAP y and x]
  2. -12 + x = 4y [Move -12 to the left side of the equivalence symbol]
  3. [-12 + x]\4 = g(x) [Divide by 4]

If you are ever in need of assistance, do not hesitate to let me know by subscribing to my You-Tube channel [USERNAME: MATHEMATICS WIZARD], and as always, I am joyous to assist anyone at any time.